The effect of good corporate governance on firm value with financial performance as a moderator - WARDANA, YUFI MAHENDRA; ANDI KUSUMAWATI; NIRWANA (International Journal of Multidisciplinary Research and Studies, 2023)
The purpose of establishing a company is to provide welfare for shareholders. However, this welfare can be hampered by a conflict of interest between the agent and the owner of the company. This study aims to prove the effect of good corporate governance as a proxy for audit committees and independent commissioners on firm value with financial performance as a moderator. This research method uses multiple regression analysis with the moderated regression analysis (MRA) approach and is helped by SPSS 25 software. In direct testing, it shows that the audit committee has no effect on firm value, and the independent board of commissioners has a positive effect on firm value. In testing the moderating variable, financial performance has a positive effect on the relationship between the independent board of commissioners and firm value. With the limited resources of the writer, it becomes a suggestion to be able to expand proxies for good corporate governance variables.